Nitisaram : the essence of polity and code of conduct - Menon, K. P. A. (Delhi, 1999)
This book is actually means is the essence of Niti, means the proper code of conduct for a human being.It is the compilation containing more than 120 verses has been in circulation in Kerala.
Keywords: Sanskrit literature